“Laughing in the Face of Patriarchy”: The Role of Gendered Humor in Mafalda by Quino (University of Bucharest Review. Literary and Cultural Studies Series, 2025)
Comics for children have a unique ability to entertain and educate young readers. Often dismissed as comical or unserious, comics are actually an important form of literature that can have a profound impact on children’s beliefs and values. This article will examine various approaches to feminist humor in the context of cultural studies in Mafalda, a popular Argentine comic strip that ran from 1964 to 1973, created by cartoonist Quino. The comic features a precocious and socially aware six-year-old girl named Mafalda, who frequently comments on politics, philosophy, and social issues, criticizing societal norms and structures. She constantly grapples with and questions the societal, political, and moral landscapes of her time, making astute observations that prompt readers to reflect on the complex world she is navigating. Beyond the humor and light-hearted exchanges, Mafalda emerges as a significant cultural text. It seamlessly intertwines entertainment with critical reflection, offering its audience not just a moment of leisurely reading but also compelling them to reckon with the profound questions and critiques articulated by its young protagonist. The use of humor in Mafalda not only serves as a form of critique but also empowers young girls and challenges the dominant gender narratives, because the comic employs gendered humor as a means of challenging traditional gender roles and stereotypes. This article explores the role of humor in Mafalda, specifically in relation to gender and how it challenges gender norms and expectations, ultimately offering a new perspective on gender and power dynamics in comics and beyond.
Keywords: Mafalda; Quino; Argentina; comic strips; humor; feminism